Natureza, liberdade, sentimento: Hans Jonas e a ética pela via afetiva - Veríssimo, Renata Franco (2023)
Thephilosophical reflectionproposedbyHansJonas is indeedrelevant, considering that thefundamental elementsof theproblemheaddresseshaveintensifiedsincethe publication of his magnumopus, "The Imperative of Responsibility'' (1979). The unlimitedandunpredictablepowerof technology,ofwhichJonasmayhavewitnessed onlytheinitialsigns, findsfertilegroundinconsumersocietyandunfoldsintoalarming, perhaps irreversible, threats to the continuity of living conditions for adiversityof speciesonplanetEarth, includinghumans.Theintentionof thisresearchistofocuson naturethroughthe lensof Jonas. Inthefirst chapterof thedissertation, thegoal isto highlight theimpactofdualismandanexacerbatedutilitarianviewof theworldbrought about bymodern science. This perspective is practiced byhumanswhoconsider themselves sovereign and detached from their surroundings. In the subsequent chapters, theresourcesutilizedbyJonas toovercomeanthropocentricmyopiawillbe exposed. Heanchorshisapproach inDarwinian theoryand invokes the impulseof freedom, establishing all living beings as ethical subjects beyond humans. Consequently, Jonasnotonlyconceptuallydeconstructshumansuperiorityoverother livingentitiesbutalsoderivesfromit theindispensableunderstandingofasolidarityof interestsbetweenhumansandnature.Thefinal chapteraims topresentJonas'snew ethical approach,whichemploysascienceof hypothetical prediction to, throughthe heuristicof fear,prevent theimaginedharmfromoccurring.Thisunderscorestheneed forvoluntaryrestraint intheconductof technologicalcivilization,whichjeopardizesnot only itselfbutalsofuturegenerationsandtheconceptofhumanity.Jonas'smaneuver involves ontologically grounding duty and biologizing moral being. But how to incorporate nature into ethical subjectivity? This is the question that guided the research,transformedintoadissertation